The Palmar and Plantar Anatomy of Dromiciops gliroides Thomas, 1894 (Marsupialia, Microbiotheria) and its Relationship to Australian Marsupials - Martin, Gabriel Mario (2017)
The monito del monte Dromiciops gliroides Thomas, 1894, is a marsupial endemic to the temperate rainforests of Argentina and Chile. Studies on its phylogenetic relationships show the species is more closely related to Australian marsupials than to any other American taxon. The study of the palmar and plantar anatomy in this species through direct observation of more than 86 specimens and comparisons with American and Australian marsupials show the pattern of D. gliroides is derived from the ancestral mammalian pattern. Dromiciops gliroides show the presence of a single palmar/plantar pad in the position of interdigital pad 1 and the lack of a thenar pad (or the complete fusion between both pads), a pattern that appears closer to some Australian diprotodont marsupials. Also shared with several Australian marsupials is the transverse orientation of pad ridges, a condition that is not shared with most arboreal/scansorial American marsupials (e.g., Caluromys spp., Marmosa spp., Marmosops spp.).